The Effect of the Use of Instagram Social Media on the Effectiveness of Da'wa Messages on the @gusmiftah Account among Teenagers - Chairiyah, Ummy; Achmad, Fandi; Arida , Vera; Falasifah , Nihlatul (Proceedings of International Conference on Da'wa and Communication, 2021)
Social media is not only used to find information but also as a means of conveying religious teachings. Many cleric use social media to spread Islam. Currently, da'wah is packaged neatly, creatively, and innovatively without reducing the message conveyed. This research is entitled The Effect of Instagram Social Media on the Effectiveness of Da'wa Messages. This study aims to determine how much influence the use of social media Instagram has on the effectiveness of da'wa messages. This type of research is quantitative research and the instrument used is a questionnaire. Using the theory of mass communication effects and simple regression test in the data analysis technique. The validity of the data is obtained through validity and reliability. Based on the results of the simple regression test that has been carried out in this study, the value of r = 0,829 and has a coefficient of determination of 75,9%. This shows that there is a positive and very strong relationship between the effect of using social media on the effectiveness of da'wah by 75,9%. Keywords: social media, Instagram, effectiveness, da'wa.